2021
DOI: 10.3390/ma15010029
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and Microstructure-Based Stress Analyses of TiNbZrTa Composite Films

Abstract: Background: the clinical application of orthopedic or dental implants improves the quality of the lives of patients. However, the long-term use of implants may lead to implant loosening and related complications. The purpose of this study is to deposit titanium (Ti)-niobium (Nb)-zirconium (Zr)-tantalum (Ta) alloys on the surface of Ti-6Al-4V to increase structural strength and biocompatibility for the possible future application of implants. Materials and methods: Ti, Nb, Zr, and Ta served as the materials for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Deposition of a niobium/zirconium/tantalum alloy on the surface of Ti-6Al-4V had shown unchanged expression of the alkaline phosphatase gene ( ALPL ) in human osteosarcoma cells (MG-63). Additionally, the surface treatment with Nb promotes better performance of L-929 mouse cells attachment to the modified surface as evidenced by higher RT-QPCR rates of type I α1-collagen and fibronectin 1 , ensuring earlier osteogenic differentiation [ 54 ]. A biocompatibility study performed on osteogenic cells from newborn rat calvaria with a G4-Ti-35 niobium alloy did not reveal any change in the following bone biomarkers: alkaline phosphatase , runx-2 , osteocalcin and osteopontin [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deposition of a niobium/zirconium/tantalum alloy on the surface of Ti-6Al-4V had shown unchanged expression of the alkaline phosphatase gene ( ALPL ) in human osteosarcoma cells (MG-63). Additionally, the surface treatment with Nb promotes better performance of L-929 mouse cells attachment to the modified surface as evidenced by higher RT-QPCR rates of type I α1-collagen and fibronectin 1 , ensuring earlier osteogenic differentiation [ 54 ]. A biocompatibility study performed on osteogenic cells from newborn rat calvaria with a G4-Ti-35 niobium alloy did not reveal any change in the following bone biomarkers: alkaline phosphatase , runx-2 , osteocalcin and osteopontin [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the new alloy film coating on the surface of conventional Ti-6Al-4V implants can not only retain the mechanical properties of the original implants, but also improve their biocompatibility, reduce the release of aluminum and vanadium ions, and reduce the degradation toxicity. Lai et al [225] added Ti-Nb interlayer and Ti-Nb-Zr-Ta composite film on the surface of the implant by cathode arc evaporation, and the results showed that the coating had no obvious toxic effect on cells, but had a great promoting effect on the growth of soft tissue cells, and Ti-Nb interlayer could also reduce the stress concentration inside the surface membrane.…”
Section: Thin Film Coating Of Titanium Alloymentioning
confidence: 99%